Featured Product "Mung Bean Agar" in Carangrejo Village to Reduce the Risk of Stunting - Edi Wibowo, Satrio; Nuraini, Henny; Syukroni, Azid; Sarilah (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2023)
The presentation of this superior product, green bean jelly, aims to provide an alternative to processed green beans for Posyandu mothers. By looking at the ingredients in it, it is hoped that it can help the process of improving nutrition for children, pregnant women, and mothers after giving birth. Apart from that, the ingredients in green beans can also help prevent stunting. Seeing the relatively high stunting rate in Carangrejo Village was the reason for choosing this superior product, green bean Jelly.